Suicide Inhibition of Cytochrome P450 Enzymes by Cyclopropylamines via a Ring-Opening Mechanism: Proton-Coupled Electron Transfer Makes a Difference - Zhang, Xiaoqian; Li, Xiao-Xi; Liu, Yufang; Wang, Yong (Frontiers in Chemistry, 2017)
N-benzyl-N-cyclopropylamine (BCA) has been attracting great interests for decades for its partial suicide inactivation role to cytochrome P450 (P450) via a ring-opening mechanism besides acting as a role of normal substrates. Understanding the mechanism of such partial inactivation is vital to the clinical drug design. Thus, density functional theoretical (DFT) calculations were carried out on such P450-catalyzed reactions, not only on the metabolic pathway, but on the ring-opening inactivation one. Our theoretical results demonstrated that, in the metabolic pathway, besides the normal carbinolamine, an unexpected enamine was formed via the dual hydrogen abstraction (DHA) process, in which the competition between rotation of the H-abstracted substrate radical and the rotation of hydroxyl group of the protonated Cpd II moiety plays a significant role in product branch; In the inactivation pathway, the well-noted single electron transfer (SET) mechanism-involved process was invalidated for its high energy barrier, a proton-coupled electron transfer (PCET(ET)) mechanism plays a role. Our results are consistent with other related theoretical works on heteroatom-hydrogen (X-H, X = O, N) activation and revealed new features. The revealed mechanisms will play a positive role in relative drug design.